O modelo de excelência de gestão do prêmio nacional da qualidade - PNQ: análise da evolução dos critérios de excelência - Moreno, José Alexandre [UNESP] (2008)
In the 1990s the Brazilian Administration launched the PBQP - Programa Brasileiro da Qualidade e Produtividade (Brazilian Program of Quality and Productivity) aiming to bring the Brazilian industry up to date by promoting improvement quality and productivity in products and processes. The year 1992 saw the first edition of the PNQ - Prêmio Nacional da Qualidade (National Quality Award), created by the FPNQ - Fundação para o Prêmio Nacional da Qualidade (Foundation for the National Quality Award), today known as FNQ - Fundação Nacional da Qualidade ( National Quality Foundation), in order to promote excellence in organization management by the adoption of the best management practices. PNQ foundations and criteria are reviewed annually to follow the evolution of management practices throughout the world. The objective of this study is to bring to light the contribution given by the PNQ to the operations and process management and organizational performance by means of a review of the history of the PNQ Excellence Foundations and Criteria from 1992 up to the 2008 cycle. A list of main performance indicators used by PNQ winning companies throughout the 16 cycles, reflecting criteria corresponding to Process Management, is given as part of the contribution by this study to the Operations and Process Mangement. It is hoped that this study will foster further research about the contribution by the PNQ Excelence Criteria to the practices of operations and process management.